Pengaruh Pemberian Pupuk Kandang Sapi Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium cepa var. Agregatum L.) Lokal Wamena - Sumiyati Tuhuteru (Agrifarm : Jurnal Ilmu Pertanian, 2022)
Manure is the group of organic fertilizers that play a role in increasing the biological, chemical and physical activities of the soil so that the soil becomes fertile and good for plant growth. The use of manure in Wamena is not yet significant because the community believes that organic farming is actually agriculture without involving any input other than planting seeds. This study aims to determine the effect of cow manure on the growth and yield of local varieties of Wamena shallots and to determine the appropriate dosage of cow manure for onion growth and yield. The study was was using a Randomized Block Design (RBD) consisting of 4 doses of cow manure, that is without treatment of cow manure (S0), treatment doses of 50 g/polybag (S1), treatment doses of 100 g/polybag (S2), and treatment doses of 150 g/polybag (S3). If the statistical test results show a significantly different effect, then it is further tested using the LSD (Least Significant Difference) at the 5% test level. The results showed that effect of cow manure had an influence on the growth and yield of local Wamena varieties of shallots, which was shown by the treatment of S2 (100 g/polybag) on the parameters of plant height of 5 MST and fresh weight of plant leaves of 9 MST. Whereas S3 (150 g/polybag) treatment gave the best effect on the number of leaves at 1 MST, leaf fresh weight and leaf dry weight.